A metal-catalyzed new approach for α-alkynylation of cyclic amines. Issue 6 (11th December 2018) - Cui, Yifan; Lin, Weilong; Ma, Shengming
Abstract : The first catalytic α-alkynylation of cyclic amines with the help of the N -propargylic group with an exclusive high E -stereoselectivity has been realized. Abstract : The first catalytic α-alkynylation of cyclic amines with the help of the N -propargylic group to afford 2-(1-alkynyl) N -allylic cyclic amines with an exclusive E -stereoselectivity for the in situ formed CC bond has been realized. Based on mechanistic studies, it is proven that the reaction proceeds through metal-mediated anti -1, 5-hydride transfer forming an iminonium intermediate, which accepts the addition of the in situ generated 1-alkynyl metal species. The synthetic application has also been demonstrated.